Knowledge as the basis for forming the innovative potential of the organization staff - I. N. Ivanov; L. V. Orlova (Вестник университета)
The article is devoted to the development of innovative potential of the personnel based on knowledge management. The controversy surrounding the concept of innovative potential is highlighted. Current trends in human resources management are described. The interpretation of the aforementioned concept as a dynamic process of self-development of the personnel is substantiated. Key competencies, dynamic, organizational and absorbing capabilities of an enterprise that are being formed as part of the knowledge management system created at the enterprise are included in the list of the main characteristics of the stated potential. It is stressed that continuous staff training should be the main block of the system. The need to integrate the knowledge management system into the innovative business model of the organization is substantiated. Therefore, the company will transform into a self-learning one and eventually, with the maximum number of employees involved in the continuous training system, a company of intellectual resources that does not only accumulate but also capitalises knowledge. It is stated that corporate universities and educational centers established at organizations should become an effective way to accumulate and share corporate knowledge.